Principles Of Thinking In Terms Of System Objectives, System Boundaries And System Structure For System Thinking In Islamic Education - Yumesri, Yumesri; Badarusyamsi, Badarusyamsi; Jamrizal, Jamrizal; Asrulla, Asrulla (Innovative: Journal Of Social Science Research, 2024)
In this article, the author tries to raise the issue of the principles of systematic thinking within the framework of the purpose of the system, the limitations of the system, and the structure of the system for systematic thinking in Islamic education. The author's interest in exploring this theme is to delve deeper into the principles of systematic thinking reviewed from the purpose of the system, the limitations, and the structure of the system for systematic thinking in Islamic education. Subsequently, in this study, the author uses a literature review method. The results of this study show that, in principle, every system always consists of four elements: an object that can be a part, an element, or a variable; attributes that determine the quality or characteristics of the ownership of the system and its object; internal relationships between the objects within it and the environment; and the place where the system is located. The limitations of the system can be physical or conceptual. The limitations of the structure of Islamic education systems in Indonesia are greatly limited by several factors, including the development of science and technology, the development of society, the development of the economy, the development of Islamic politics, the development of religion, and the growing culture of society. The system must be interconnected between one component and another component.